Graphene exfoliation in cyrene for the sustainable production of microsupercapacitors - Pedro Moreira; David Carvalho; Rodrigo Abreu; Maria D Alba; Joaquín Ramírez-Rico; Elvira Fortunato; Rodrigo Martins; Joana Vaz Pinto; Emanuel Carlos; João Coelho (JPhys Energy)
Graphene and its composites have attracted much attention for applications in energy storage systems. However, the toxic solvents required for the exfoliation process have hampered the exploitation of its properties. In this work, graphene dispersions are obtained via liquid phase exfoliation (LPE) of graphite in cyrene, an environmentally friendly solvent with solubility parameters like those of N-methyl-2-pirrolidone. The obtained dispersions with a concentration of 0.2 mg ml ^−1 comprised multilayered graphene sheets with lateral sizes in the hundreds of nanometers, as confirmed by scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy. Mixing the obtained dispersions with ethanol made it possible to collect the graphene, which was redispersed in 2-Propanol. This active material was used to fabricate supercapacitor electrodes using a scalable spray deposition method on carbon nanotube (CNT) current collectors with the aid of vinyl masks. The device, tested with a PVA/LiCl gel electrolyte, achieved a specific capacitance of 3.4 mF cm ^−2 (0.015 mA cm ^−2 ). In addition, the devices show excellent cycling stability (>10 000 cycles at 0.5 mA cm ^−2 ) and good mechanical properties, losing less than 10% of initial capacitance after 1000 bending cycles. This work demonstrates the adaptability of liquid-phase exfoliation to produce graphene sustainably, providing the proof-of-concept for further 2D materials processing and green microsupercapacitor (MSC) fabrication.